DAMPAK KEBERADAAN INDUSTRI BESAR DAN SEDANG DI DAS KALIGARANG HULU TERHADAP KUALITAS AIR PASOKAN PDAM KODIA SEMARANG1 - Zaenuri Mastur; Kusni Kusni; Nurkaromah Dwidayatl (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2003)
Every production process of material for producing something with machinery aid that is operated by human being, will produce the product and residue. Residue from production proces is called waste. Large and medium industrial development have effect to water qualitiy. The purpose of this research is to study the impact of the large and medium manufacturing industry in Kaligarang Hulu Area on water quality of PDAM input of Kota Semarang. The research variable sare ( 1) type of large and medium manufactory,(2) the water quality of Kaligarang, and industry waste. For reaching that aim, we carried out test to water quality of Kaligarang and waste outlet of industry, in terms of pH, BOD, COD,TSS, Zn 2+, and Pb2+. Act of ditermination of the large and medium industry existing of sampling with purpose sampling technique, where as sample with composite sampling methode. The amount of sample is 5, that is (1) Genuk, Ungaran, (2) Karangtengah, Bandarjo, (3) Tinjomoyo, (4) Jembatan Besi Kradenan and (5) PDAM. Analysis by descriptive comparative. Based on laboratorium test, pH concentration is 7,59 - 7,73. TSS between 35,1 - 184,ppm, BOD and COD each of them are 1,9 - 5,3 ppm and 3,27 - 8,99 ppm, where as concentration of Zn 2+ and Pb2+ is ppm. They are under standarization of Governor establishment. There were 4 factors, that are (1) a part of waste gut.ter is turned out. to river in Pedalangan, (2) relative small waste debite, (3) the waste gutter was turbulance, and (4) the research was carried out in raining season. The recomendation are: (I) iffluent and stream standard monitoring in terms of pH, BOD, COD, TSS, Zn, 2Pb2 continously; (2) mapping of household industry a long Kaligarang river.